New connections between brand and environmentally sustainable businesses in the Amazon forest and local business owner’s perception - Luiz Diego Vidal Santos; Francisco Sandro Rodrigues Holanda; Pedro Vinícius Bertulino de Menezes; Catuxe Varjão de Santana Oliveira; Ana Paula Schervinski Villwock; Alceu Pedrotti (Sustainable Earth Reviews)
Abstract The debate surrounding entrepreneurship in the Amazon rainforest region highlights the importance of sustainable actions developed by local brands. However, limited attention has been given to entrepreneur's perspectives regarding the outcome of their applied practices. The objective of this study was to understand the entrepreneurs’ perception based on their business models concerning the connection to the Amazon brand and the aspects of sustainable use of its natural resources. The study was performed through semi-structured interviews with seven Amazonian product brands entrepreneurs utilizing Grounded Theory. The results demonstrate that entrepreneurs understand that reaching the social dimension relies on the articulation of three main factors: entrepreneurs, the native people, and the shared traditional knowledge and culture. It is observed that the political dimension is still underdeveloped in the region with limited application of its effects on products. Additionally, the economic dimension is not significantly favored by the utilization of environmentally sustainable brands. Lastly, the territorial dimension depends on the establishment of permanent protection areas, as well as agroforestry systems.